A method to design vibratory bowl feeder by using FEM modal analysis - Le, Giang-Nam; Nguyen, Van-Mui; Dang, Anh-Tu (Vietnam Journal of Science and Technology, 2019)
This paper presented a digital simulation study, using the finite element method with modal analysis on the ANSYS Workbench platform, to determine the fundamental frequencies of the mechanical system and to affirm the design and manufacture parameters of the vibratory bowl feeders. Then an experiment was conducted to verify the results. The results suggest that the simulation model can be used to identify parameters of the bowl’s structure before the device is manufactured.